2005
DOI: 10.1016/j.bbadis.2005.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The C2 variant of human serum transferrin retains the iron binding properties of the native protein

Abstract: The tryptic digests of blood samples obtained from transferrin C1 and C2 (TfC 1 and TfC2 hereafter) genotypes were analysed by Liquid Chromatography coupled to Electrospray Mass Spectrometry (LC/ESI--MS/MS). The analytical results confirmed the single base change in exon 15 of the Tf gene. The solution behaviour and the iron binding properties of the two Tf variants were studied by UV-visible spectrophotometry and by circular dichroism. It appears that TfC2 globally manifests the same spectral features as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Feder et al 18 suggested that, although both the HFE C282Y and the HFE H63D proteins are dysfunctional, HFE C282Y may be more so; any dysfunction associated with the transferrin C2 protein is yet to be established. 19 The damaging effects of the at-risk combinations were limited to those without dementia and were not seen in those with fully developed Alzheimer's disease. This is consistent with the view that misregulated iron and the associated oxidative stress exert their harmful influence in the preclinical phase of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Feder et al 18 suggested that, although both the HFE C282Y and the HFE H63D proteins are dysfunctional, HFE C282Y may be more so; any dysfunction associated with the transferrin C2 protein is yet to be established. 19 The damaging effects of the at-risk combinations were limited to those without dementia and were not seen in those with fully developed Alzheimer's disease. This is consistent with the view that misregulated iron and the associated oxidative stress exert their harmful influence in the preclinical phase of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…2D, Table S9). While this variation in transferrin has long been recognized, no appreciable differences in iron binding or other activities have been discerned between C1 and C2 ( 22 ). However, this polymorphism occurs only two amino acids away from position 591, which is sufficient to control TbpA binding (Fig.…”
mentioning
confidence: 99%
“…12,[14][15][16][17]21 Yet the protein encoded by the C2 transferrin allele may have similar function to the transferrin wild-type allele. 14,27 In this study transferrin C1/C2 alleles alone or in combination with the HFE C282Y gene variant were not associated with AMD. These data suggest that the potential involvement of iron and transferrin in modulating oxidative injury in AMD is not related to different function of the C1/C2 alleles.…”
Section: Discussionmentioning
confidence: 79%